MODIFICATION OF TESTS IN ASSESSING LANGUAGE SKILLS (Academicia Globe: Inderscience Research, 2022)
This article aims to analyze types of assessment and tests. Their appropriateness to the learner’s skills and talents. Modification of tests according to the knowledge and interests of the learners.